Management of Patient with Aggressive Periodontitis by Orthodontic and Prosthodontic Collaboration - Chaterina Diyah Nanik. K; Anindita Apsari (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2017)
Background: One of the most common inflammation disease in the oral cavity for the past few years is the aggressive form of periodontitis. Common signs of aggressive periodontitis is the mobility of teeth especially in incisive and first molars, and occuring mostly in young patient. Young patients whose losing her anterior teeth, are a real challenge for dentist and prosthodontist. Prosthodontist need to consider both functional and esthetic aspects. Objective: Rehabilitation of young adult patient with aggressive periodontitis by an interdisciplinary approach of orthodontist and prosthodontist. Case Description: A young woman, suffered from aggressive periodontitis with major complain of her teeth mobility, especially incisive and first molar in mandible. She had undergone periodontal treatment, but the result was failed. The anterior teeth in mandible need to be extracted, therefore patient wished not to be in edentulous state. As preliminary treatment, we choose immediate denture to replace the anterior mandible teeth. We faced difficulties in mandible, because her right canine weren’t in the proper dental arch. So we asked orthodontist to place fixed orthodontics in mandible, to get the canine back in the proper arch. We’ve chosen orthodontic treatment,because we didn’t want to extract the canine teeth. We evaluated in six months and after the canine back in the proper arch, we proceed to long span bridge in mandible as our definitive treatment. Conclusion: By not extracting the canine teeth, we got some advantages, especially patient psychically was happier with her own teeth. The collaboration with another dentistry field, provides us better treatment for patient. After treatment, patient had no complaints and was happy with her new smile.